Uma introdução a econofísica: através de história em quadrinhos - SOUZA, Márcio Wagner de Araújo (2024)
Econophysics is a discipline that uses the principles of statistical physics to analyze economic phenomena, such as the behavior of shares in the financial market, among others. An alternative to disseminating and teaching econophysics to the public who have no knowledge of this area, is through the creation of educational products such as comic books, which are teaching resources that retain the attention and awaken the imagination of readers, in addition to facilitating understanding difficult concepts through simple, visual and playful language. The objective of this work is to present an educational product such as comic books to explain the main concepts and applications that involve this area, as well as studies and new approaches. The methodology for developing this educational product consists of creating a script for a comic book that addresses econophysics in a simple and objective way, bringing out the main concepts that involve this interdisciplinary area of physics.